RAPID CT Perfusion–Based Relative CBF Identifies Good Collateral Status Better Than Hypoperfusion Intensity Ratio, CBV-Index, and Time-to-Maximum in Anterior Circulation Stroke - Potreck, A.; Scheidecker, E.; Weyland, C.S.; Neuberger, U.; Herweh, C.; Möhlenbruch, M.A.; Chen, M.; Nagel, S.; Bendszus, M.; Seker, F. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: Information of collateral flow may help to determine eligibility for thrombectomy. Our aim was to identify CT perfusion–based surrogate parameters of good collateral status in acute anterior circulation ischemic stroke.MATERIALS AND METHODS: In this retrospective study, we assessed the collateral status of 214 patients who presented with acute ischemic stroke due to occlusion of the MCA M1 segment or the carotid terminus. Collaterals were assessed on dynamic CTA images analogous to the multiphase CTA score by Menon et al. CT perfusion parameters (time-to-maximum, relative CBF, hypoperfusion intensity ratio, and CBV-index) were assessed with RAPID software. The Spearman rank correlation and receiver operating characteristic analyses were performed to identify the parameters that correlate with collateral scores and good collateral supply (defined as a collateral score of ≥4).RESULTS: The Spearman rank correlation was highest for a relative CBF < 38% volume (ρ = −0.66, P < .001), followed by the hypoperfusion intensity ratio (ρ = −0.49, P < .001), CBV-index (ρ = 0.51, P < .001), and time-to-maximum > 8 seconds (ρ = −0.54, P < .001). Good collateral status was better identified by a relative CBF < 38% at a lesion size <27 mL (sensitivity of 75%, specificity of 80%) compared with a hypoperfusion intensity ratio of <0.4 (sensitivity of 75%, specificity of 62%), CBV-index of >0.8 (sensitivity of 60%, specificity of 78%), and time-to-maximum > 8 seconds (sensitivity of 68%, specificity of 76%).CONCLUSIONS: Automated CT perfusion analysis allows accurate identification of collateral status in acute ischemic stroke. A relative CBF < 38% may be a better perfusion-based indicator of good collateral supply compared with time-to-maximum, the hypoperfusion intensity ratio, and the CBV-index.AUCarea under the curveHIRhypoperfusion intensity ratioIQRinterquartile rangemCTAmultiphase CTArCBFrelative CBFsCTAsingle-phase CTATmaxtime-to-maximum